Implementation of Nawaz, Enscore, and Ham (NEH) for Minimize Makespan in Job Shop Scheduling - Adistyas Nastiti, Octavia; Sukmono, Tedjo (International Journal on Orange Technologies, 2025)
OPQ is a company that specializes in providing construction materials such as ready-mix concrete, precast concrete, concrete bricks and crushed stone. With 4 different compositions and high demand, it is not uncommon for problems to occur, namely late delivery. This research aims to increase work efficiency by minimizing makespan to reduce idle time which will impact delays in product delivery to customers. The results of production scheduling using the NEH method produce smaller makespan results and faster production process completion times compared to the scheduling method used by the company. The NEH method produces a makespan of 2.29 with the job sequence P3-P4-P2-P1. The method used by the company obtained a makespan of 3.01 with a partial work sequence of P2-P3-P4-P1. This can prove that the calculation results using the NEH method can minimize makespan and this method can be used by companies as a reference for scheduling the production process to overcome the problems being faced by the company.